Model of effectiveness for NCR private secondary schools - Pobocan-Donozo, Tara Chavez (Animo Repository, 2004)
This research develops a model of school effectiveness for private secondary schools in the National Capital Region. To achieve such objective, the attributes of three groups of schools are compared and contrasted. These three groups are the foreign effective schools, 5 low-performing schools, and 10 top-performing schools. The attributes of the foreign effective schools are taken from a comprehensive review of literature that concentrates on school effectiveness research and on the actual experiences of identified effective schools abroad. Nine school dimensions are investigated: (1) administrators, (2) teachers, (3) students, (4) parents, (5) staff, (6) written curriculum, (7) instruction, (8) evaluation, and (9) school environment. Qualitative data analysis is used. The research techniques employed are interview, survey-questionnaires, documentary analysis, and observations. In this research, it is revealed that the top-performing schools significantly differ from lowperforming schools. Although the top-performing schools and the foreign effective schools largely share similar attributes, there are still marked differences between the two groups. What are formulated in this research are three major theories: (1) a model of the current practice of NCR top-performing schools, (2) the ideal attributes of an effective school (Ecube School), and (3) a model of school effectiveness for NCR private secondary schools (Ecube Arrow).